SOMETIMES-POOL ESTIMATOR OF RELIABILITYFUNCTION OF EXPONENTIAL DISTRIBUTION FOR TIMECENSORED DATA - Kashmar, Ali (Iraqi Journal of Science, 2024)
A condense study was done for Some times -pool estimator of reliability functionof exponential distribution for time concord data. The estimator ( )~2 R t is adjusted tobe( ) {[exp( | )] [exp( | ( ˆ ˆ ] }~2 0 R 1 1 2 2 R R t  t  I  nt K n  n  IWe proposed the estimator( ) {[exp( ˆ (1 ) )] [exp( ( ˆ ˆ ) | ( )] }~3 1 0 R 1 0 1 2 0 0 1 2 R R t  tK   K  I  t n r  n r n  n I Study and derivative the equation of bias, MSE, size of data, and relative efficiencyfor the proposed estimator and compare with similar and classical estimators, andgiven some numerical results to show the efficiency of propose estimator